THE DECLINE IN SOCIALIZATION AT THE TRANSITION FROM CLASS TO SUBJECT TEACHING IN THE INCLUSION - Subotić, Siniša; Anđić, Branko (Specijalna edukacija i rehabilitacija, 2014)
The goal of this research was to explore the potential socialization drop that might occur when students transition from class teaching (i.e. having mainly one teacher) to subject teaching (i.e. having many teachers). We had two competing assumptions: 1) that the socialization drop will affect both typically developed (TD) and so called special educational needs (SEN) students, and 2) that the drop will affect SEN students more. Using a transversal approach and sociometric method we tested these assumptions on a sample of 685 (55 SEN) elementary school children from the Republic of Srpska, grades four through nine. The results clearly supported the second assumption. While sociometric social preference for TD children did not change through the grades, SEN children social preference dropped significantly at the transitional sixth grade, never again to recover to the fourth grade level, when there was no difference between SEN and TD children. This effect was only slightly affected by the peer discipline issues nominations. Thus, when trying to design potential socialization support and intervention programs in inclusion, we should be aware of the expected transitional socialization drop. Keywords: inclusion, socialization, sociometry, elementary school